Dispersal limitation of Tillandsia species correlates with rain and host structure in a central Mexican tropical dry forest. - Elizabeth Victoriano-Romero; Susana Valencia-Díaz; Víctor Hugo Toledo-Hernández; Alejandro Flores-Palacios (PLoS ONE)
Seed dispersal permits the colonization of favorable habitats and generation of new populations, facilitating escape from habitats that are in decline. There is little experimental evidence of the factors that limit epiphyte dispersion towards their hosts. In a tropical dry forest in central Mexico, we monitored the phenology of dispersion of epiphyte species of the genus Tillandsia; we tested experimentally whether precipitation could cause failures in seed dispersal and whether seed capture differs among vertical strata and between host species with high (Bursera copallifera) and low (Conzattia multiflora) epiphyte loads. With the exception of one species that presents late dispersion and low abundance, all of the species disperse prior to the onset of the rainy season. However, early rains immobilize the seeds, affecting up to 24% of the fruits in species with late dispersion. We observed that Tillandsia seeds reach both Bursera and Conzattia hosts, but found that adherence to the host is 4-5 times higher in Bursera. Furthermore, seeds liberated from Bursera travel shorter distances and up to half may remain within the same crown, while the highest seed capture takes place in the upper strata of the trees. We conclude that dispersion of Tillandsia seeds is limited by early rains and by the capture of seeds within the trees where populations concentrate. This pattern of capture also helps to explain the high concentrations of epiphytes in certain hosts, while trees with few epiphytes can be simultaneously considered deficient receivers and efficient exporters of seeds.